The rest is still unwritten: female adolescents' cultivation of gender from MTV's reality television series "The Hills" through celebrity gossip blog commentary - Seeger, Loren A. (Kansas State University, 2009)
The purpose of this study is to research cultivation effects of gender represented on MTV reality television series "The Hills" on adolescent female bloggers. Gerbner’s cultivation theory structures the background of this study. By conducting a textual analysis of various celebrity gossip blog sites from November 1-30, 2008, this study will unveil personal opinions relating to the reality of constructed gender representation and authenticity of "The Hills" as a “reality” television program. Blogs provide an ambiguous platform for individuals to immediately express opinions, judgments and attitude concerning the program; therefore, this study will be a contribution to the expanding field of convergence and “new media.” Although comments on the websites are critical of "The Hills" characters and their depiction of “reality,” the television program has a dedicated audience, calling for the reevaluation of “fandom.” Cyberspace offers an opportunity for virtual dialogue among viewers, as well as a platform to express cyberfeminist rhetoric. Women and girls are gaining new social and organizing space, claiming a new form of power and shaping media and society through particular kinds of participatory communication.
Keywords: Cyberfeminism; Reality television; Blogs; Gender; The Hills; MTV; Mass Communications (0708); Women's Studies (0453)